PORTRAIT OF HARMONY BETWEEN MUSLIMS AND CHRISTIANS (CASE STUDY IN KELET VILLAGE, KELING DISTRICT, JEPARA REGENCY) - Wahyu Khoiruz Zaman (Jurnal Scientia, 2023)
This study aims to: find out how the harmony that occurs in Kelet Village towards the form of harmony to attitudes and social interactions that occur in Kelet Village, Keling District, Jepara Regency. The data collection methods used are: 1) observation, is the basis of science carried out by making observations and systematic records of the elements seen in an object of study; 2) interviews, is a method of collecting data by communicating which is used to obtain data on the harmony that occurs between Muslims and Christians in Kelet Village; 3) documentation, to document data sources used to complete the research is carried out by collecting data in the form of written sources, images and monumental works that can add information for researchers. The analysis used by researchers is to use a type of field research research, namely research where the researcher directly conducts research in a structured manner and takes data from the field or information directly by visiting respondents. This research uses a qualitative approach, namely as a research method that intends to understand a phenomenon, about what the object of research experiences from behavior, motivation, perception and describe with natural words and language.